Navigating Digital Transformation in E-learning at Bangladesh's Tertiary Level: Prospects and Challenges - Fahmida Haque (European Scientific Journal, ESJ, 2025)
In the 21st century, Higher Education Institutions have prioritized digital shift as an apparent and essential process for their institutions. In the face of the growing importance and demands of digital incorporation into the classroom and examination process, the HEIs in Bangladesh continue to impart online education even after the pandemic. Having this backdrop, the present research aims to identify the challenges that the HEIs in Bangladesh are facing in implementing digitalization. Since the present study aims to respond to the research questions of a qualitative and quantitative nature, data collection and analysis techniques from both methodologies are implemented, and the Mixed Method Research approach has been chosen as the methodology of this research. The study employed convenient sampling and involved a total of 100 students - 50 from two public universities and 50 from two private universities in Bangladesh. Additionally, we included 10 teachers, with an equal distribution of 5 from public and 5 from private universities. Data was gathered through written survey questionnaires and interviews conducted with the participants. The study's findings revealed several significant challenges faced by higher education institutions (HEIs) in Bangladesh as a result of digital transformation. Key issues include a lack of a clear strategic vision (50%), inadequate policy and legislative frameworks (45%), insufficient digital literacy among stakeholders (83%), unreliable internet connectivity (33%), ineffective outcome-based digital teaching and learning platforms (67%), and serious concerns regarding digital campus network information security (83%). Additionally, financial constraints (67%), limited technological support (67%), insufficient data enablement solutions (48%), underutilized artificial intelligence capabilities (49%), and a scarcity of digital academic library resources (63%) further exacerbate the situation. To address these challenges, the study offers several recommendations. These include formulating a strategic vision for digital transformation and modernizing the curriculum and Learning Management Systems (LMS). Furthermore, a proposed framework for “digital maturity” is put forth, enabling HEIs to evaluate their current digital strategies and improve them through the integration of various enterprises and methodologies.